Priporočila za zagotavljanje kakovosti prehranskih dopolnil - Pravst, Igor (Farmacevtski vestnik, 2012)
Food supplements are foods, intended to supplement the normal diet. They are concentrated sources of individual or combined nutrients or other substances with nutritional or other physiological effects and are usually on the market in the form of capsules, tablets, pills and other similar forms such as powder in sachets, liquid in ampoules, drop dispensing bottles and other similar forms designed to be used in measured small unit quantities. Dietary supplements should be safe to use, marketed and presented in a way not to mislead the consumer, their composition must correspond to the label until the end of product shelf life when stored according to the manufacturer's instructions. These recommendations provide assistance to operators in providing quality of food supplements, and a basis for assessing the quality of dietary supplements on the market.
Keywords: kakovost; kontrola kvalitete; prehranska dopolnila; security; varnost